WEEKEND EFFECT ON HIBOR: TEST OF A STRUCTURAL CHANGE - Gordon Y. N.; Billy S. C. Mak (Asian Academy of Management Journal, 1996)
Seasonality has been one of the popular issues in the finance literature. Fama (1965) is one of the earlier researchers who reported seasonality in stock markets. Using the US data, Fama found that the variance on Monday is greater than that for other days. Cross (1973) also showed that negative Monday returns exist in the US stock market. French (1980), Keim and Stambaugh (1984), and Cornell (1985) provided recent evidences on seasonality on stock markets. They showed that the mean stock return on Monday is significantly negative while that on Friday is significantly positive Although this anomaly is first found in the US stock market empirical evidences also exist for other stock markets (Jaffe and Westerfield, 1985) Besides numerous research on daily stock returns. Rogalski (1984) found that the Weekend effect is valid only from February to December and the negative Monday effect occurs from Enday close to Monday open. Harris (1986) further examined the seasonality using intraday data of NYSE stocks He found that the negative Monday returns is attributed by non-trading period as well as by the beginning session of Monday morning.